Corpus of Joe Bailey : a novel - Hall, Oakley M. (Viking Press, 1953)
This story covers twenty years in the lives of Joe Bailey and his family and friends. It begins in 1928 in the Mission Hills neighborhood of San Diego, when Joe is eleven and learns of the death of his mother. It continues with teen-age experiences during the Depression, goes on to fraternity life at Berkeley, pretty much skips Joe's experiences in World War II, and ends with his efforts to settle in to postwar America. Many other characters enter into the story, particularly Con, a childhood friend who later becomes his lover. Through it all Joe copes with his insecurities, which manifest themselves in different ways during different episodes and stifle his attempts to find direction to his life.